Subsistence and semi subsistence agriculture in Romania - Mihaela Cristina Vlad (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The paper aims to analyze the main question that arises in the context of current agricultural policies: are households farms really? Viewed from the perspective of sustainable development of rural areas, the answer becomes very important, especially given that the actual shortcomings rural employment opportunities and business development. Research is needed, especially given the new Common Agricultural Policy for the period 2014-2020 still provides annual grants (between 500-1000 euros), especially given that you want to implement a policy of restructuring. In order to eliminate the sector subsistence farmers producing for own consumption only occasionally provides a scheme for granting annuities 2020 for owners who will give lands on lease or be sold to commercial farms and co financing up to 15,000 euros for starting a business.
Keywords: 330; individual households; subsidies; sustainability